2016
DOI: 10.1021/acs.jmedchem.6b00995
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Noncovalent, Mutant-Selective Epidermal Growth Factor Receptor Inhibitor

Abstract: Inhibitors targeting the activating mutants of the epidermal growth factor receptor (EGFR) have found success in the treatment of EGFR mutant positive non-small-cell lung cancer. A secondary point mutation (T790M) in the inhibitor binding site has been linked to the acquired resistance against those first generation therapeutics. Herein, we describe the lead optimization of a series of reversible, pan-mutant (L858R, del T790M/L858R, and T790M/del) EGFR inhibitors. By use of a noncovalent double mutant (T790M/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…In order to improve the activity against the activating single and double mutants of EGFR, the substituted piperidine was replaced by an N-alkylsulfonylpyrazole, leading to one of the most potent compounds 26f. 15 Compound 26f exhibited comparable activity against the EGFR T790M/L858R and EGFR T790M/del (746-750) mutants and improved activity against the L858R and del (746-750) single mutants, while also showing improved activity against EGFR WT . The X-ray complex of compound 26f and EGFR T790M/L858R suggested that the hydrogen bonds between the sulfonylpyrazole group and Lys745, and the hydrophobic interactions formed between the cyclopropyl group and Phe723 were responsible for the increased activity relative to the piperidinecontaining series ( Figure 20B).…”
Section: Aminopyrimidine Compoundsmentioning
confidence: 93%
See 3 more Smart Citations
“…In order to improve the activity against the activating single and double mutants of EGFR, the substituted piperidine was replaced by an N-alkylsulfonylpyrazole, leading to one of the most potent compounds 26f. 15 Compound 26f exhibited comparable activity against the EGFR T790M/L858R and EGFR T790M/del (746-750) mutants and improved activity against the L858R and del (746-750) single mutants, while also showing improved activity against EGFR WT . The X-ray complex of compound 26f and EGFR T790M/L858R suggested that the hydrogen bonds between the sulfonylpyrazole group and Lys745, and the hydrophobic interactions formed between the cyclopropyl group and Phe723 were responsible for the increased activity relative to the piperidinecontaining series ( Figure 20B).…”
Section: Aminopyrimidine Compoundsmentioning
confidence: 93%
“…One of the most potent compounds, 26e (Figure ), bearing a cis ‐fluorohydroxypiperidine, a hydroxyethyl group, and a trifluoropropyl group displayed surprising potency against EGFR T790M/L858R and EGFR T790M/del (746‐750) , with 125‐fold selectivity over EGFR WT and promising efficacy in a xenograft model. In order to improve the activity against the activating single and double mutants of EGFR, the substituted piperidine was replaced by an N ‐alkylsulfonylpyrazole, leading to one of the most potent compounds 26f . Compound 26f exhibited comparable activity against the EGFR T790M/L858R and EGFR T790M/del (746‐750) mutants and improved activity against the L858R and del (746‐750) single mutants, while also showing improved activity against EGFR WT .…”
Section: Third‐generation Inhibitors Overcoming Egfrt790mmentioning
confidence: 99%
See 2 more Smart Citations
“…Exon 18 and 20 mutations result loss of P772, H773, and the addition of P, C, and Q amino acids, respectively [8][9][10] . The double mutations occurred in EGFR-TKD by T790M/L858R (TMLR) and T790M/del 746−750 (TMdel) is also known as point mutation 11,12 .…”
Section: Introductionmentioning
confidence: 99%